Building resilience for future adversity: a systematic review of interventions in non-clinical samples of adults - Macedo, Tania; Wilheim, Livia; Gonçalves, Raquel; Coutinho, Evandro Silva Freire; Vilete, Liliane; Figueira, Ivan; Ventura, Paula (BMC psychiatry, 2014)
Potentially traumatic events happen in people's lives, leading to the risk of the development of posttraumatic stress disorder, depression and even suicide. Resilience is an individual's ability to maintain or regain his/her mental health in the face of significant adversity or risk of death. The aim of this study was to conduct a systematic review of studies evaluating the effectiveness of resilience promotion interventions in adults. Electronic searches were conducted in databases ISI, PsycINFO and PubMed, including every language and every year until January 20, 2013. We selected studies with nonclinical samples of adults that evaluated the effectiveness of the intervention through randomized and non-randomized controlled trials and open-ended studies. We also considered valid constructs directly related to resilience, such as hardiness. Among 2.337 studies, 13 were selected for the review, 5 through electronic databases and 8 through search in references or the "times cited list" (list of articles that cited the selected papers). Of these, 7 are randomized controlled trials, 5 non-randomized controlled trials, and one an open-ended trial. Most of the studies included reported some degree of improvement in resilience-like variables among those subjects exposed to resilience-promoting programs. Furthermore, positive findings were more consistent among randomized controlled trials--six out of the seven suggested efficacy. There is evidence pointing towards some degree of effectiveness of resilience promotion programs, despite the poor operationalization of the construct and great heterogeneity in the studies. Indeed, the analysis of the methodological quality of the selected studies was hampered by the poor quality of reporting. There were faults in reporting in most studies on almost all items (random sequence generation, allocation concealment, blinding of outcome assessment, incomplete outcome data, description of concurrent treatment and intent-to-treat analysis), except for the item "selective reporting". Additional efforts should be made to determine the actual effect size of the interventions, since this is crucial for calculating the cost-effectiveness of resilience promotion strategies.